A graph-theoretic model of single point mutations in the cystic fibrosis transmembrane conductance regulator - Kakraba, Samuel; Knisley, Debra (JOURNAL OF ADVANCES IN BIOTECHNOLOGY, 2016)
Cystic fibrosis is one of the most prevalent inherited diseases. This disease is caused by a mutation in a membrane protein, the cystic fibrosis transmembrane conductance regulator (CFTR). CFTR is known to function as a chloride channel that regulates the viscosity of mucus that lines the ducts of a number of organs. The most prevalent mutation of CFTR is located in one of two nucleotide binding domains, namely, the nucleotide binding domain one (NBD1). However, some mutations in nucleotide binding domain two (NBD2) can equally cause cystic fibrosis. In this work, a graph-theoretic model is built for NBD2. Using this model for NBD2, we examine the consequences of single point mutations on NBD2. We collate the wildtype structure with eight of the most prevalent mutations and observe how the NBD2 is affected by each of these mutations.